Counselling Placements Caught up in the Mismatch of Standards And Realities: Lessons From COVID-19 - Pelden, Sonam; Banham, Vicki (Journal of University Teaching and Learning Practice, 2020)
As the fear of mortality struck humanity, a new age dawned in the relational styles, processes, and interactions amongst people. COVID-19 has caused a major shift in the educational landscape. While most teaching and learning activities moved online, field placement units which are fully invested in industry engagement, and once highly sought, came to a dramatic pause. For students, this produced uncertainty around completion of their degrees and for institutions who became entangled in the changing requirements of accrediting bodies as they grappled with the changing landscape. Our final year counselling and psychotherapy students on placement were instructed to retreat from their placements while some ‘lucky few’ joined the drifting warriors working from the safety of their homes with their assigned agencies. Crisis and contemporary times call for openness and innovation grounded in practical wisdom. But the tyranny of COVID-19 times highlighted a growing gap between professional standards and community realities. This paper alludes to the struggles of counselling postgraduate University students on placement who are caught up in the mismatch between professional standards of accreditation bodies and the emerging community expectations and practices. It draws on literature to highlight the impact of historic controversial discourses involving online counselling and face-to-face counselling on current practices. This paper aims to reflect on lessons dispensed by COVID-19 to the professional bodies and universities in order to work together in creating innovative, non-placement work-integrated learning (WIL) practices that reflect the realities within the current landscape.